Eficacia del diagnóstico molecular SARS CoV-2 por inactivación a calor en saliva e hisopado cornete frente extracción hisopado nasofaringeo Iquitos 2021 - Shapiama López, Wagner Valentino (2023)
The purpose of this project was to establish a real-time PCR assay for the detection of SARS-CoV-2 that would use a non-invasive biological sample such as saliva or mid-turbinate swab that would provide results in a short period of time and that would support SARS CoV-2 diagnostic procedures in Iquitos city. This project aimed to compare the internal effectiveness positivity, sensitivity, specificity, and positive predictive value of a molecular diagnostic test for SARS-CoV-2 using extracted RNA from saliva and mid-turbinate swabs versus heat extraction of the same biological samples. This is a cross-sectional, prospective, analytical study. A total of 289 participants were enrolled after they requested a real-time PCR test to detect SARS CoV-2 at the reference laboratory of the Regional Government of Loreto. The Centers for Disease Control of the United States validated primers and probes. The difference between the sensitivity, specificity, and positive predictive value of the real-time PCR test using extracted RNA and heat-inactivated biological samples were not statistically significantly different, p-value> 0,05, proving that both assays were effective.